Differences of sex and subject area in Chilean university students in the province of Concepcion, Chile - Navarro Saldaña, Gracia (2016)
This research explores sex and discipline-area differences in empathy across theInterpersonal Reactivity Index developed by Davis. A descriptive cross-sectionalstudy was performed with the participation of 680 university students, divided into351 women and 329 men belonging to Physics-Mathematics, Social-Humanisticand Biological-Chemistry areas. The results show sex differences in threedimensions of the inventory with higher scores for women. No differences inrelation to the subject area of the students were observed. There is interactionbetween sex and discipline in the mathematical-physicist women who obtainedhigher scores in Personal Distress than other participants.